Increasing Product Distribution Capacity and Financial Management Of â€œKampungâ€ Chicken Egg Business at Lau Dendang Traditional Chicken Farm - Sianipar, Aryanti Sariartha; Adika Fajar Putra; Fauziah Kumalasari (Talenta Publisher, 2022)
There are several types of chicken farms with various production models. In the production process, partners start by purchasing chicken seeds and providing vitamins and then raising them by providing natural animal feed in the form of vegetables and fruits from traditional markets, so they do not use manufactured animal feed such as pellets and the like. Then, the enlargement process takes 3-5 months. In the husbandry principle, partners use the cage-free principle. However, in the production process, partners still use natural equipment due to limited capital. In addition, partners' knowledge of product marketing management is still minimal, even though the concept of organic production can be a potential brand that differentiates compared to competing products. On the financial management side, the business still combines personal and business finances, there is no clear cash flow report periodically. This causes the business to have no clear profit/loss and relatively slow to develop. Through this program, the implementation team offered solutions in the form of providing machines to facilitate the distribution of goods and increase the capacity of livestock land, providing branding concepts through brands and counseling on simple business financial management principles. The targeted outputs are increased egg production capacity, reduced feed distribution and transportation costs, added value in the form of brands, and simple business financial reports.